Renewable diesel as fossil fuel substitution in Malaysia: A review - Chia S.R.; Nomanbhay S.; Ong M.Y.; Shamsuddin A.H.B.; Chew K.W.; Show P.L. (Elsevier Ltd, 2023)
Carbon monoxide; Coal liquefaction; Diesel engines; Diesel fuels; Environmental impact; Feedstocks; Sustainable development; Bio-oil refining; Bio-oils; Biological upgrading; Clean energy; Fischer-Tropsch process; Hydroprocessing; Hydrothermal liquefactions; Malaysia; Oil refining; Renewable diesels; Fischer-Tropsch synthesis